The use of technical chlorine for seawater sterilization in the rearing of barramundi larvae Lates calcarifer - Ni Wayan Widya Astuti; Indah Mastuti; I Made Sedana; Sunarto Sunarto; Mustakim Mustakim; I Nyoman Suwitra; Mujiono Mujiono; Kurdi Kurdi; Luh Yuliani Dewi; Kadek Mas Tantra; Katimin Katimin; Ja'far Shadiq; Ahmad Muzaki (Depik, 2025)
Disease prevention is very important in the rearing of barramundi larvae, one of which is by sterilizing the seawater using technical chlorine. This study aimed to determine the effect of seawater sterlization use technical chlorine for rearing barramundi larvae on growth, survival, and water quality. The treatment in this study was different seawater used for water exchange during larval rearing. Seawater was sterilized with 25 ppm technical chlorine for 24 hours. Before use, the water was neutralized using 12.5 ppm sodium thiosulfate. As a control in this study, direct seawater or untreated sea water was used for water exchange. The study was conducted with 3 replications. The parameters observed in this study were growth, survival, virus monitoring, growth variation, and water quality. Sterilization of seawater with 25 ppm technical chlorine used for rearing larvae of barramundi has no significant effect on growth, survival, growth variation and water quality of rearing larvae. The use of filtered seawater is recommended in the sterilization of seawater for rearing larvae of barramundi. Increasing the dose of chlorine or using chlorine which has a high active substance could increase effectiveness of water sterilization.Keywords:Technical chlorineSterilizationRearing larvaeBarramundiLates calcarifer